ANALISIS DAN PEMODELAN SIMULASI DAMPAK LINGKUNGAN PENAMBANGAN BATU ANDESIT MENGGUNAKAN METODE SISTEM DINAMIK (Studi Kasus : Penambangan Batu Andesit di desa Salawangi Kecamatan Bantarujeg Kabupaten Majalengka) - Nisa Farhatunnisa; Deffy Susanti; Ardi Mardiana (PROCEEDING STIMA)
The existence of a stone quarry project area will affect the surrounding environment of a region. In addition due to the damage to the road infrastructure, the activities of the miners who perform processes like mine, the waste rock fragments, erosion, fresh water resources is reduced, etc., which will continue to accumulate in accordance with the development of the population the number of rock miners, the activities of miners and environmental components. A similar condition is the presence of stone mining project located in the Village District of Bantarujeg Salawangi. This study uses a matrix ofLeopold to identify the state of the initial environmental setting in the village, through the interview method. Further research conducted by the dynamic simulation modeling approach that provides comprehensive results that the project area will be undergoing expansion by utilizing the andesite quarry material which is influenced by population number of miners, mining project activity. The role of government to improve the condition shown by increased supervision and counseling, the environmental impact can be minimized. This simulation uses a span of 10 years. Simulations using the Ventana Simulation Software PLE x32.Keywords: Matrix Leopold, Mining Project, Dynamic Simulation Modeling, Simulation Software Ventana PLE x32.